Antioxidant Activities and Protective Effects of Shorea macrophylla Leaf and Bark Extracts - Ramli, Salfarina; Sukri, Nik Nor Sabrina; Zulkifli, Nur Adhwa’ Faqihah; Ariestanti, Donna Maretta; Choo, Chee Yan; Halim, Hasseri; Manshoor, Nurhuda; James, Richard Johari (Pharmaceutical Sciences and Research, 2024)
Shorea macrophylla, also known as the ‘Engkabang’ tree or Light Red Meranti, is renowned for its role in reforestation efforts. Despite lacking records of traditional use, the reported biological activities of other species within the Shorea genus spark curiosity about the potential biological activities of this plant. Therefore, this study aims to explore the antioxidant capabilities of S. macrophylla leaf and bark extracts, along with their protective effects against oxidative stress using a brine shrimp model. In the evaluation of antioxidant potential, 2,2-diphenyl-1-picrylhydrazyl (DPPH) and ferric reducing antioxidant power (FRAP) assays were employed. Extracts were incubated in DPPH and FRAP solutions, and absorbances were measured at 517 and 593 nm, respectively. The brine shrimp lethality assay (BSLT) involved exposing brine shrimps (Artemia salina) to various concentrations of the extract, with LC50 values determined through probit regression analysis. Oxidative stress protection assays entailed treating brine shrimps with safe doses of S. macrophylla extracts before exposure to H2O2, with subsequent observation of survival rates. The DPPH assay unveiled IC50 values of 1.025 and 0.693 mg/mL for S. macrophylla leaf and bark extracts, respectively, while FRAP values exhibited a concentration-dependent relationship. BSLT demonstrated concentration-dependent mortality, with LC50 values of 0.93 and 0.6455 mg/mL for S. macrophylla leaf and bark extracts, respectively. Pre-treatment with S. macrophylla extracts significantly increased brine shrimp survival against H2O2-induced oxidative stress. In conclusion, both S. macrophylla leaf and bark water extracts demonstrated noteworthy antioxidant activities and exhibited protective effects against oxidative stress in brine shrimps. These findings provide insights into the antioxidant activities and protective effects of S. macrophylla Leaf and Bark extracts.